2020
DOI: 10.1111/jen.12833
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic, thermal and trophic responses of a predatory ladybird Cheilomenes propinqua

Abstract: Diapause which enhances survival during unfavourable periods is one of the most common seasonal adaptations of insects. A typical 'diapause syndrome' includes an arrest of development (or of reproduction is the case of adult diapause), a decrease in metabolism, an increase in the resistance to adverse environmental conditions, an accumulation of reserves, etc. In contrast to quiescence, facultative diapause is an 'anticipatory response', that is it is induced by environmental cues before the beginning of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…These ranges of temperatures were used because we presumed that the storage temperature at the rearing facility can be strictly controlled, whereas the transportation conditions can vary considerably. Regarding the long-term experiment, our (unpublished) pilot test demonstrated that at temperatures of 10 °C and lower C. propinqua adults are not able to feed, whereas the results of our previous study [ 28 ] suggest that feeding on some factitious food is necessary for their long-term storage. On the other hand, another earlier study [ 30 ] showed that at 20 °C (in contrast to 15 °C) C. propinqua females matured and laid eggs, suggesting that the temperature of 20 °C is too high for long-term storage.…”
Section: Methodsmentioning
confidence: 62%
See 3 more Smart Citations
“…These ranges of temperatures were used because we presumed that the storage temperature at the rearing facility can be strictly controlled, whereas the transportation conditions can vary considerably. Regarding the long-term experiment, our (unpublished) pilot test demonstrated that at temperatures of 10 °C and lower C. propinqua adults are not able to feed, whereas the results of our previous study [ 28 ] suggest that feeding on some factitious food is necessary for their long-term storage. On the other hand, another earlier study [ 30 ] showed that at 20 °C (in contrast to 15 °C) C. propinqua females matured and laid eggs, suggesting that the temperature of 20 °C is too high for long-term storage.…”
Section: Methodsmentioning
confidence: 62%
“…To start the experiment, a cohort of the first instar larvae hatched over 24 h from eggs laid by 10–20 C. propinqua females was reared on the green peach aphid at a temperature of 25 °C and L:D = 10:14, i.e., under the short-day conditions that increase the survival of starving females [ 28 ]. The emerging adults were kept in groups of 20–50 individuals under the same conditions for 5 more days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, feeding some coccinellids on alternative or low-quality essential food results not only in the delay or termination of oogenesis but also in the decrease of metabolism, the accumulation of fat, and other components of the adult (reproductive) diapause. This so-called 'trophic diapause' has been demonstrated not only in predatory [13][14][15][16][17][18][19][20] but also in phytophagous ladybirds [21,22]. Thus, food can have a double impact on the reproduction of coccinellids: (1) 'signal' effect (as an environmental diapause-inducing or diapause-averting cue) and ( 2) 'nutritional' effect (specific nutrients are necessary for oogenesis).…”
Section: Introductionmentioning
confidence: 99%